Artificial Intelligence and Education. An analysis from Agnotology - Matas-Terrón, Antonio (My University, 2022)
The starting point. What's ignorance? Ignorance is a condition in which a person has no knowledge regarding something or doesn't have information regarding a topic or an issue. Ignorance can also be defined as the absence of insight, understanding, or even education in the sense of training.
Slides presentation introducing the Agnotology as academical discipline.
Keywords: Inteligencia artificial; Education; Agnotology; Ignorance